Opportunities and Challenges of Applying Cognitive Process Dimensions to Map-Based Learning and Alternate Assessment - Bechard, Sue; Karvonen, Meagan; Erickson, Karen (Frontiers in Education, 2021)
In education, taxonomies that define cognitive processes describe what a learner does with the content. Cognitive process dimensions (CPDs) are used for a number of purposes, such as in the development of standards, assessments, and subsequent alignment studies. Educators consider CPDs when developing instructional activities and materials. CPDs may be one way we are able to track students’ progress toward acquiring increasingly complex knowledge. There are a number of terms used to characterize CPD, such as depth-of-knowledge, cognitive demand, cognitive complexity, complexity framework, and cognitive taxonomy or hierarchy. The Dynamic Learning Maps (DLM™) Alternate Assessment System is based on a map-based model where academic domains are organized by cognitive complexity based on the literature appropriate for the diversity of students with significant cognitive disabilities (SCD). Of these students, approximately 9% either demonstrate no intentional communication system or have not yet attained symbolic communication abilities. This group of students without symbolic communication engages with and responds to stimuli in diverse ways based on context and familiarity. Most commonly used cognitive taxonomies begin with initial levels, such as recall, that assume students are using symbolic communication when they process academic content. Taxonomies that have tried to extend downward to address the abilities of students without symbolic communication often include only a single dimension (i.e., attend). The DLM alternate assessments are based on learning map models that depict cognitive processes exhibited at the foundational levels of pre-academic learning, non-symbolic communication, and growth toward higher levels of complexity. DLM examined existing cognitive taxonomies and expanded the range to include additional cognitive processes that demonstrate changes from the least complex cognitive processes through early symbolic processes. This paper describes the theoretical foundations and processes used to develop the DLM Cognitive Processing Dimension (CPD) Taxonomy to characterize cognitive processes appropriate for map-based alternate assessments. We further explain how the expanded DLM CPD Taxonomy is used in the development of the maps, extended standards (i.e., Essential Elements), alternate assessments, alignment studies, and professional development materials. Opportunities and challenges associated with the use of the DLM CPD Taxonomy in these scenarios are highlighted.